The Influence of Emotional Intelligence and Quality of Work Life on Intention to Leave of Civil Servants: Role of Satisfaction as Mediator - Widodo, Djoko Setyo (Archives of Business Research, 2023)
This study aims to describe and explain the effect of emotional intelligence and quality of work life on job satisfaction and intention to leave of the civil servants. The type of research is quantitative descriptive used and methods that are verificative. The research location is the hinterland in the Kalimantan region. Data collection is done by observation, interviews and questionnaires given to civil servants interviews and questionnaires given to 395 civil servants in the hinterland in the Kalimantan region. The result of this study is that based on SEM analysis using Lisrel it is known that emotional intelligence and work quality of life have a significant effect on both Job Satisfaction and intention to leave of Civil Servants. Likewise Job Satisfaction has a significant effect on the intention to leave of the Civil Servants and mediates the relationship between emotional intelligence and quality of work life with the intention to leave of the civil servants. This research succeeds in revealing novelty, namely: "Improving the Job Satisfaction can be done by considering factors of emotional intelligence and work quality of life to lower numbers of intention to leave of the Civil Servants. For this reason, these factors must be prioritized by government in an effort to improve the Job Satisfaction of the civil servants